الاليات القانونية لحماية العقارات المشعة في الجزائر (مجلة الواحات للبحوث والدراسات, 2017)
The Algerian Legislature Is Interested In Real Estate، Like Other International Legislations، And This Interest Is Embodied In The Civil Law As A Public Law And An Arsenal Of Laws And Decrees Related To Urban Development And Real Estate Promotion، Which Came In Turn With Legal Rules Protecting The Environment Taking Into Account The Nature Of Non-Renewable Resources As Land And Built-Up Spaces Linked To Green Spaces، Which Requires Rationalization Of Land Use And Customize To Sustainable Development. The Legislator Also Intervene Within The Conduct، Controland Removal Of Waste Act Through A Series Ofprotecting Rules From Any Kind Of Waste Pollutionbecause Humans Are Linkedto Ecosystems، Which Sometimes Requires A Reconsideration Of The Real Estate Or Forgotten Or Marginalized Sites.And We Mean Here Real Estate Exposed To Radioactive Contamination Due To The French Nucleartests. Key words - Radioactive pollution, realty, Nuclear experiments, environmental protection, environmental damage, environmental compensation